Antenatal Care (ANC) Coverage, Health Infrastructure, and Postnatal Care (PNC) Services Utilization: A District Level Analysis of Punjab-Pakistan - Gillani, Seemab; Ahmad, Tusawar Iftikhar; Wang, Feng; Shafiq, Muhammad Nouman (iRASD Journal of Economics, 2021)
Awareness of receiving postnatal care is uncommon in Punjab (Pakistan) and supply-side is also unfortunate. Sufficient uptake of PNC may helpful in reducing maternal mortality. Thus, this study explored the demand and supply-side determinants of maternal health (utilization of PNC) care for 35 districts of Punjab, Pakistan. Percentage of women of reproductive ages using PNC services in the 35 districts of Punjab was the outcome variable. While, ANC utilization, adult literacy rate, household wealth, physical infrastructure had been considered as the explanatory variables. Secondary data were obtained from Punjab Development Statistics reports from the years 2010 to 2016. Pooled ordinary least square (OLS) and Generalized Method of Moments (GMM) were applied as estimation techniques. It was found that the percentage of women of reproductive ages using ANC services (0.662, p < 0.01), the percentage of households receiving remittances from abroad (0.570, p < 0.01), the percentage of households having access to improved sanitation facilities (0.569, p < 0.01), the percentage of households having their own houses (0.530, p < 0.05), and district-based health infrastructure index (0.237, p < 0.05) had strong positive and significant impact on PNC utilization. The study concluded that district-based targets relating to PNC coverage could be achieved by intervening through ANC utilization behavior, household wealth (remittances receipts), and through the provision of infrastructure (healthcare, sanitation) to the residents of the district. Need to ensure the availability and accessibility of PNC in order to reduce the health disparities among the districts of Punjab.